(untitled) (Clinics, 2021)
OBJECTIVES: To determine the rate of and main risk factors for postoperative infection in cancer patients who underwent spine surgery in the last 5 years in order to determine whether there is an association between postoperative infection and increased mortality during hospitalization. METHODS: All cancer patients who underwent surgical procedures between January 2015 and December 2019 at a single hospital specializing in spine cancer surgery were analyzed. The primary outcome of interest was postoperative infection. Bivariate logistic regression was used to estimate the odds ratio and 95% confidence interval for each variable in relation to the occurrence of infection. RESULTS: We evaluated 324 patients, including 176 men (54.3%) and 148 women (45.7%) with a mean age of 56 years. The incidence of postoperative infection was 20.37%. Of the 324 patients, 39 died during hospitalization (12%). CONCLUSIONS: Surgical time greater than 4 hours, surgical instrumented levels greater than 6, and an Eastern Cooperative Oncology Group of 3 or 4 were associated with an increased risk of postoperative infection, but these factors did not lead to an increase in mortality during hospitalization.